Secondary Metabolite Compounds from Alpinia monopleura Extract and Evaluation of Anti-Inflammatory Activity based on In Vitro and In Silico Studies - Yodha, Agung Wibawa Mahatva; Badia, Esti; Musdalipah; Reymon; Fauziah, Yulianti; Fusvita, Angriani; Arfan; Wahyuni; Sahidin (Bogor Agricultural University, Indonesia, 2024)
Alpinia monopleura is one of the endemic plants of Sulawesi, and it has an extensive distribution in the region. Research on chemical compounds and biological activities of A. monopleura is essential to continue as an effort to support the utilization of native plants for medicine. The extract was obtained using the maceration method. The chemical compounds in the extract were identified using Liquid Chromatography Mass Spectrometry (LCMS). Bovine Serum Albumin (BSA) and molecular docking methods were used to evaluate the anti-inflammatory activity. Ten compounds contained in the extract were successfully identified, E-para-coumaric acid (1), trans-ferulaldehyde (2), 3,5,6-trihydroxy-4',7-dimethoxyflavone (3), nevadensin (4), malvalic acid (5), ent-16α,17-hydroxy-19-kauranoic acid (6), 3′,5-dihydroxy-7,4'-dimethoxy flavone (7), saurufuran B (8), 5-hydroxy-7,8,2'-trimethoxyflavanone (9) and dehydroabietic acid (10). The anti-inflammatory activity of extracts from rhizomes and stems of A. monopleura were 8.62 and 10.59 mg/L, respectively. Some flavonoids (9 and 7) can bind strongly to specific residues around the COX-2 active site, such as Ser530, thereby interfering with the function of the COX-2 enzyme and reducing the production of pro-inflammatory prostaglandins. Thus, A. monopleura extract has the potential to inhibit inflammatory responses through molecular regulation of the COX-2 enzyme.